The Influence Of The Values Of The 8 Pillars Of Human Relations Path On The Formation Of Students' Religious Character At Al Ma'shum Mardiyah Integrated Junior High School, Cugenang District, Cianjur Regency - Nizar Abdullah Suja'i; Umar Burhanudin; Arina Fadhilah Jannah (Doctoral Program of Social Science Pasundan University, 2026)
This research is motivated by the phenomenon of less than optimal implementation of religious values ????in students at school, such as low discipline in worship, lack of social awareness, and minimal parental role in supporting character building at home. This creates a gap between the values ????taught and students' daily behavior. Al Ma'shum Mardiyah Integrated Junior High School tries to bridge this gap through the application of the values ????of the 8 pillars of human relationships, including relationships with Allah SWT, the Prophet Muhammad SAW, parents, teachers, others, older people, younger people, and the environment. The purpose of this study is to determine the extent of the influence of the values ????of the 8 pillars of human relationships on the formation of religious character of students at Al Ma'shum Mardiyah Integrated Junior High School, Cugenang District, Cianjur Regency. The research method uses an associative quantitative approach with Stratified Random Sampling technique. Data were collected through observation, questionnaires, interviews, and documentation. Data analysis was carried out using normality tests, linearity, simple regression, coefficient of determination, and t-test. The results of the study showed a regression coefficient of 0.726, which is included in the strong category, with the contribution of variable X to Y of 52.7%, while 47.3% is influenced by other factors outside the study. The t-test obtained a calculated t-value of 12.3502, which is greater than the t-table of 2.0930, with a significance of 1.59 × 10?1?< 0.05. This proves that there is a significant influence of the values ??of the 8 pillars of the human relationship path on students' religious character. Thus, the null hypothesis (H?) is rejected and the alternative hypothesis (H?) accepted.